1994
DOI: 10.1144/gsl.qjegh.1994.027.p2.03
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical aspects of sabkha at Jubail, Saudi Arabia

Abstract: A large industrial complex was planned to be sited at Jubail on the Gulf Coast of Saudi Arabia. The sabkha here is essentially a near sea level, fiat area of fine grained soils, partially cemented by salt (sodium chloride) and calcium sulphate. Very little carbonate was found. The rest of the site was covered by sand dunes which, further inland, reached a height of 30 m.The presence of artesian water, detected and measured at widespread locations, probably conducted through fissures in the underlying Hadrukh b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…They are highly heterogeneous and exhibit behaviour ranging from non-plastic to highly plastic, with liquid limits as high as 80% or more. More detailed information on sabkha soils is provided by James and Little [22], Hossain and Ali [13], Akili [3] and Akili and Torrance [4]. In coastal areas, coral limestone formations, which, in their natural condition, are soft, non-homogeneous and porous, and can be challenging for foundation designers.…”
Section: Geotechnical Profilesmentioning
confidence: 99%
“…They are highly heterogeneous and exhibit behaviour ranging from non-plastic to highly plastic, with liquid limits as high as 80% or more. More detailed information on sabkha soils is provided by James and Little [22], Hossain and Ali [13], Akili [3] and Akili and Torrance [4]. In coastal areas, coral limestone formations, which, in their natural condition, are soft, non-homogeneous and porous, and can be challenging for foundation designers.…”
Section: Geotechnical Profilesmentioning
confidence: 99%
“…These bonds can be lost upon wetting with water and, hence, the strength can be significantly decreased (Al-Amoudi et al, 1997;Shehata and Lotfi, 1993). These evaporites form a hard crust when dry, however, a person got sunk to his knee when the crust was wetted (Akili and Ahmad, 1983;Al Amoudi, 1995;James and Little, 1994;Sabtan and Shehata, 2002;Shehata et al, 1989;Shehata et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…They usually form in hot, arid climates and are associated with shallow groundwater tables (A1-Amoudi & Asi 1991). Artesian conditions, although of marginal significance, have been reported to exist in some of the eastern Saudi sabkha terrains (James & Little 1994;A1-Guwaizani 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The collapse potential presents an unacceptable risk in normal practice and calls for the improvement of their mechanical properties prior to any construction. A1-Amoudi (1993) reported that for many large-scale construction projects, elaborate techniques such as dynamic compaction, densification piles, stone columns, extensive underdrainage and geotextiles have been employed (Juillie & Sherwood 1983;James & Little 1994). For small-scale structural projects (e.g.…”
Section: Introductionmentioning
confidence: 99%